Black dahlia & white rose - Oates, Joyce Carol, 1938- (Ecco, 2012)
In this work the author offers a collection of 11 previously uncollected stories, including a title piece that tracks the friendship between Elizabeth Short, famously known as the Black Dahlia, the victim of a markedly brutal murder in 1940s Los Angeles that remains unsolved, and her roommate, Norma Jeane Baker who became Marilyn Monroe.